Ivabradine drug utilization study in five European countries: A multinational, retrospective, observational study to assess effectiveness of risk‐minimization measures. Issue 11 (4th September 2019) - Salem, Linda; Malouvier, Alexandre; Blatchford, Jon; Rivero‐Ferrer, Elena; Deltour, Nicolas; Jacquot, Emmanuelle
Abstract: Purpose: This drug utilization study of ivabradine evaluated prescriber compliance with the new risk minimization measures (RMMs), communicated starting 2014 following preliminary results from the SIGNIFY study. Methods: This was a multinational (five European countries) chart review study with two study periods: pre‐RMM and post‐RMM. Patients initiating ivabradine for chronic stable angina pectoris in routine clinical practice were identified across general practitioners and specialists. The primary outcome analysis evaluated the compliance with the new RMMs, ie, use in patients with a heart rate greater than or equal to 70 bpm at initiation, no doses higher than those recommended in the summary of product characteristics (SmPC) at initiation and during 6 months of follow‐up, and no concomitant use of verapamil or diltiazem. Results: Overall, 711 and 506 eligible patients were included in the pre‐RMM and post‐RMM periods, respectively. The percentage of patients prescribed ivabradine according to the new RMMs increased significantly in the post‐RMM period (70.6% and 78.4% in the pre‐ and post‐RMM periods respectively; P value = .0035). The compliance to RMMs increased for all the criteria assessed independently: the proportions of patients with (a) heart rate ≥ 70 bpm at initiation (79.4% and 85.2%, respectively; P value = .0141), (b) no dose higher than the SmPC doses at initiation and during follow‐up (92.8% and 94.1%, respectively; P value = .3957), and (c) no concomitance with verapamil or diltiazem (96.1% and 99.2%, respectively; P value = .0007). Conclusions: The RMMs for ivabradine were well implemented across the five participating European countries confirming a favorable benefit‐risk balance of ivabradine in chronic stable angina pectoris.